Tilapia aquaculture as a reservoir of antimicrobial resistance and zoonotic bacteria: evidence from Makassar, Indonesia - Mursalim, M.F.; Raharjo, H.M.; Kholilulloh, Z.A.; Azis, H.Y.; Nurdin, M.A.; Mar’ah, N.; Hartanti, A.P.N.; Amalia, U.; Risal, M.J.S.; Mabrok, M.; Aljasir, S.F. (Polish Journal of Veterinary Sciences, 2026)
A total of 69 bacterial isolates representing 13 species were recovered from 60 tilapia and 14 water samples. Isolates were identified via phenotypic characterization, biochemical assays and VITEK MS, and antimicrobial susceptibility was assessed using the Kirby-Bauer disk diffusion method, followed by calculation of the multiple antibiotic resistance (MAR) index. Dominant taxa included Bacillus cereus (21.7%), Plesiomonas shigelloides (17.4%) and Enterobacter spp. (15.9%), while 11.6% remained unclassified, likely reflecting limitations of the VITEK MS reference database or insufficient spectral matching. Zoonotic species such as Klebsiella pneumoniae and Acinetobacter johnsonii were also detected. Species distribution did not differ significantly between fish and water, indicating uniform microbial dissemination. Gram-negative isolates showed higher resistance than Gram-positive isolates, with multidrug resistance, particularly against erythromycin–penicillin combinations, most prevalent in Aeromonas spp. MAR indices ≥ 0.2 suggest possible exposure to environments associated with antimicrobial contamination. While water quality was generally suitable for tilapia, localized hypoxia and acidic pH may promote pathogen persistence. The coexistence of multidrug-resistant and zoonotic bacteria highlights the need for integrated health management and responsible antimicrobial use in urban aquaculture.